Discrimination and the fiscal benefits of immigration - Nicholas Lawson (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2024)
In recent decades, there has been a lengthy debate about the fiscal costs or benefits of immigration, and much of the literature has found fiscal impacts that are close to zero. However, these studies have ignored the possibility that immigrants may be victims of wage discrimination in the labour market, despite evidence of such discrimination in various countries. In the presence of such discrimination, existing estimates of the fiscal impact of immigration will be biased: if immigrants are paid less than their marginal products, then someone else is receiving that income - mostly likely the firm's owners or other workers - and paying taxes on it, and that fiscal benefit is ignored by a model that disregards discrimination. In this paper, I evaluate the quantitative importance of this mechanism, by calibrating a search-and-matching model to Canadian data and simulating the fiscal impact of increases in immigration. When the model and calibration omits wage discrimination against immigrants, the average fiscal impact of immigration is negative, but it becomes positive if discrimination explains the wage gaps between natives and immigrant workers: at an economy-wide level, an annual fiscal cost of about 3 billion in the absence of discrimination becomes a fiscal benefit of about 4 billion in the presence of discrimination. My results indicate that wage discrimination against immigrants could significantly affect our estimates of the fiscal impact of immigration.
Keywords: H27; J61; J79; 330; discrimination; immigration; fiscal benefits